Integration in the Study of Homosexuality, GLBT Issues, and Sexual Identity - Yarhouse, Mark A. (Journal of psychology and theology, 2012)
This article examines integration in the areas of homosexuality, gay, lesbian, bisexual, and transgender (GLBT) issues, and sexual identity. It provides a brief account of where we have been as a field in our attempts to bring together a Christian worldview and the study of these issues. It then moves to a discussion of where we are going as a field, as well as the challenges and opportunities that exist for Christians interested in the integration of faith and the scientific study of homosexuality, GLBT concerns, and sexual identity.